Rami Comminution Is Associated With Displacement of Minimally Displaced Lateral Compression Type 1 Injuries on Lateral Stress Radiographs. Issue 10 (October 2022) - Hadeed, Michael M.; Tucker, Nicholas J.; Heare, Austin; Mauffrey, Cyril; Parry, Joshua A.
Abstract : Objectives: To determine whether displacement on lateral stress radiographs (LSRs) in patients with minimally displaced lateral compression type 1 pelvic ring injuries is associated with any demographic and/or injury characteristics. Design: Retrospective comparative cohort. Setting: Urban level 1 trauma center. Patients/Participants: Ninety-three consecutive patients with minimally displaced lateral compression type 1 injuries. Intervention: Displacement of pelvic ring injury on LSR (≥10 mm vs. <10 mm). Main Outcome Measurements: Demographic and injury characteristics (mechanism of injury, Nakatani rami classification, rami comminution, Denis zone, complete/incomplete sacral fracture, sacral comminution). Results: 65.6% of patients (n = 61) had ≥10 mm of displacement on LSR. On univariate analysis, displacement was associated with increased age [median difference 11: confidence interval (CI), 2–23], female sex [proportional difference (PD): 25.1%, CI, 3.9%–44.4%], Nakatani classification (type I PD: 27.9%, type II PD: −19.5%), and rami comminution (PD: 55.6%, CI, 35.4%–71.3%). On multivariate analysis, displacement was only associated with rami comminution (odds ratio: 16.48, CI, 4.67–58.17). Displacement was not associated with energy of injury mechanism, sacral fracture Denis zone, complete sacral fracture, sacral comminution, or bilateral rami fractures. Conclusions: Although rami comminution was the only variable found to be independently associated with displacement ≥10 mm on LSR, no single variable perfectly predicted displacement. Future studies are needed to determine whether displacement on stress radiographs should change the management of these injuries. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.